THE EFFECT OF SERVICE QUALITY AND PRICE ON CUSTOMER SATISFACTION OF INDIHOME SERVICE USERS IN BIREUEN DISTRICT - M Hafid; Zikra Hayati; Raudhatul Jannah; Mawaddah; Agustin Nurhayati (Universitas Efarina, 2024)
The development of information technology allows the use of more sophisticated media such as the internet to make it easier to access information. PT Telekomunikasi Indonesia, Tbk (Telkom) is a telecommunications company that has a product called Indihome for surfing the internet. This study aims to determine the effect of service quality and price on customer satisfaction of Indihome internet service users in Bireuen Regency. The method used in this research is a quantitative approach. The results showed that service quality has a partial effect on customer satisfaction of Indihome internet service users in Bireuen Regency. This is indicated by the tcount> ttable value at the 5% level (2.051> 1.65993) and a significant value of 0.043 <0.05. The results showed that price has a partial effect on customer satisfaction of Indihome internet service users in Bireuen Regency. This is indicated by the value of tcount> ttable at the 5% level (5.203> 1.65993) and a significant value of 0.000 <0.05. The results showed that the value of service quality and price had a simultaneous and significant effect on customer satisfaction of Indihome internet service users in Bireuen Regency. With a value of Fhitung> Ftabel (19.511> 3.09), and a significant value (sig) = 0.000 <0.05.